The Nature and Diversity of Personal Property Security Systems in Canada - Boodman, Martin (Revue générale de droit, 1992)
In Canada, there are three natural groupings of personal property security systems. These are the Common law systems of nine provinces and two territories, the Civil law system of Québec and the Canadian federal legislation relevant to secured lending. The Common law jurisdictions subdivide into two groups consisting of those which have adopted or are about to adopt unitary personal property security legislation modelled upon Article 9 of the U.C.C. of the United States, and those which have not and are not about to adopt such legislation.The purpose of this paper is to describe the common and disparate features of the systems for security on personal or moveable property in Canada. The descriptive exercise indicates that it is impossible to characterize the law in this domain as either completely divergent or homogeneous and that, despite similarities and differences, there is a substantial degree of commensurability among Canadian systems of security on personal property.